The Mediating Effect of Sleep Quality and Burnout Toward Work Engagement among Healthcare Worker - Ahmad Naufal Darydzaky; Putri Mega Desiana (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study examines the interrelationship among job stress, work engagement, sleep quality, and burnout on JD-R Model. Moreover, this study also analyzes the mediating effect of sleep quality and burnout, which is usually a dependent variable.  Methods: This study was conducted on 236 healthcare workers from various hospitals in Indonesia. The data were collected from an online survey using a 4-Point Likert scale, which was analyzed using Lisrel 8.80 through Structural Equation Modelling (SEM). Findings: The results show that job stress is positively associated with work engagement and burnout. Sleep quality mediates job stress toward work engagement and burnout. Burnout mediates the relationship between job stress and sleep quality. This study also found that job stress was not associated with sleep quality.  Originality/Value: Many studies are competing to understand the emergence and process of burnout and work engagement. This research is heading in a different direction and focuses on exploring and analyzing the variables of burnout, job stress, sleep quality, and work engagement and their interrelationship. Practical/Policy implication: Given the results, this study recommends that healthcare workers be aware of their oath and live a healthy lifestyle. In addition, health institutions could conduct a job analysis and create HR policies that imply productivity and fairness.